Thermal and Catalytic Degradation Kinetics of High-Density Polyethylene Over NaX Nano-Zeolite - Abbas, Ammar S.; Saber, Marwa G. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Thermal and catalytic pyrolysis of waste plastics in an inert atmosphere has been regarded as a creative method, since pyrolysis can convert plastics waste into hydrocarbons that can be used either as fuels or as a source of chemicals.Natural Iraqi kaolin clay was used to synthesis the NaX nano- zeolite by hydrothermal conditions with average particle size equal to 77.63nm.Thermal decomposition kinetics of high-density polyethylene (HDPE) in the absence and presence of catalysts nano NaX Zeolite was investigated. Thermal and catalytic degradation of HDPE was performed using a thermogravimetric analyzer in nitrogen atmosphere under non-isothermal conditions 4, 7 and 10 °C/min heating rates were employed in thermogravimetric analysis (TGA) experiments.First-order decomposition reaction was assumed, and for the kinetic analysis Coats and Redfern (CR) method was used. The apparent activation energy (Ea) was evaluated. Results showed that the NaX nano-zeolite decreases the activation energy (Ea) of HDPE pyrolysis further than the thermal pyrolysis.